Translingual practice as a discursive strategy to shape lifestyle and cultural identity - Yunhong Wang; Boyang Peng; Xiaoli Tang (Humanities & Social Sciences Communications)
Abstract The paper presents a comprehensive examination of the influence of online translingual practice on the lifestyle choices and identity construction of Chinese youth. An analysis of data sourced from platforms such as Weibo and Xiaohongshu finds that the emergence of new lifestyles facilitated by translingual practice transcends traditional social norms, leading to notable shifts in lifestyle preferences. These shifts advocate for active mobility, sustainable practices, clothing habits of inclusive colors and styles, and the adoption of alternative consumption patterns that challenge entrenched standards and regulations. Translingual practice is emblematic of the broader trend towards increased diversity in lifestyle choices within Chinese society. By shedding light on how translingual practice functions as a conduit for communicating and negotiating lifestyle politics, the research offers novel insights into its pivotal role in individual and community identity formation within online spaces and its potential as a transformative force in enriching life choices and prompting action in the real world. Moreover, the study underscores the importance of understanding the rise and popularity of such lifestyles within the context of the interplay between global influences and local dynamics.